Security performance analysis of photography service system / Farah Shazwani Ismail - Ismail, Farah Shazwani (Faculty of Computer and Mathematical Sciences, 2019)
Photography business become more popular and trending among the most of people who likes photography. Photography Service System was developed to help photography companies to deliver photos and videos to their customers. The use of the system have its advantages such as easiness of accessing data and also make users share the data faster. The purpose of the system was developed to ease the daily works and can be used frequently by photography companies as a method to send photos and videos to their customers. Unfortunately, the system that developed by developer, sometimes there is a lack of security performance. A penetration testing was conducted in order to test the security performance by conducting four method of security attacks such as Denial of Service (DoS), SQL injection, Cross Site Scripting, and sniffing password. The purpose of these attacks were conducted is to testing and finding the vulnerabilities of the system because the system deals with the customers’ privacy data which is the photos and the videos owned by the customers. This is crucial to secure a system where the first step taken as a prevention to introduce the system to the public, vulnerability assessments was performed to determine the weaknesses of the system. Scanning and vulnerability assessment are done using tools which is Vega Scanning Tool, Wireshark, and Low Orbit Ion Cannon (LOIC). All results are collected and have been analyze. As a summary of the result, it shows that the system are vulnerable to DoS attack, SQL injection attack, cross site scripting and also password sniffing.